2024
DOI: 10.1002/adfm.202401684
|View full text |Cite
|
Sign up to set email alerts
|

Topological Phonons and Thermoelectric Conversion in Crystalline Materials

Zhong‐Ke Ding,
Yu‐Jia Zeng,
Wangping Liu
et al.

Abstract: Topological phononics, a fascinating frontier in condensed matter physics, holds great promise for advancing energy‐related applications. Topologically nontrivial phonons typically possess gapless edge or surface states. These exotic states of lattice vibrations, characterized by their nontrivial topology, offer unique opportunities for manipulating and harnessing energy transport. The exploration of topological phonons opens new avenues in understanding and controlling thermal transport properties, with poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 208 publications
0
0
0
Order By: Relevance
“…Yuan et al [23] emphasized the complex relationship between atomic mass, bonding characteristics, and thermal performance through their analysis of Janus XBAlY (X = Se, S, Te, Y = S, Se, O, X ̸ = Y) monolayers. Ding et al [24] by exploring topological phonons, have opened up new avenues for understanding and controlling thermal transport properties, with potential applications in thermoelectric materials, phononic devices, and waste heat recovery. By analyzing the κ of 2D materials, Gu et al [25] found that the high thermal yield materials have plane structure, and the medium κ materials have three-layer mirror symmetrical crystal structure, low κ materials have double-layer or three-layer crystal structure, but no mirror symmetry, which indicates that the κ of 2D materials is highly sensitive to crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…Yuan et al [23] emphasized the complex relationship between atomic mass, bonding characteristics, and thermal performance through their analysis of Janus XBAlY (X = Se, S, Te, Y = S, Se, O, X ̸ = Y) monolayers. Ding et al [24] by exploring topological phonons, have opened up new avenues for understanding and controlling thermal transport properties, with potential applications in thermoelectric materials, phononic devices, and waste heat recovery. By analyzing the κ of 2D materials, Gu et al [25] found that the high thermal yield materials have plane structure, and the medium κ materials have three-layer mirror symmetrical crystal structure, low κ materials have double-layer or three-layer crystal structure, but no mirror symmetry, which indicates that the κ of 2D materials is highly sensitive to crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] Searching for materials with intrinsically low lattice thermal conductivity is another avenue to obtain high TE performance materials [22,23] because this approach helps to simplify complex TE parameters and optimize TE performance. Due to their unique physical structures, low-dimensional materials possess a variety of physical properties, [24][25][26][27][28][29][30] which provides new possibilities for achieving low thermal conductivity and high TE performance. For instance, the material SnSe exhibits a high TE figure of merit as a result of its low thermal conductivity, while the half-Heusler compound PCdNa is noteworthy for its low thermal conductivity coupled with superior TE performance.…”
Section: Introductionmentioning
confidence: 99%